Assessing the safety of home oximetry for COVID-19: a multisite retrospective observational study - Jonathan Benger; Kelsey Flott; Ara Darzi; Jonathan Clarke; Hutan Ashrafian; Gianluca Fontana; Sarah Elkin; Roberto Fernandez Crespo (BMJ Open)
Objectives To determine the safety and effectiveness of home oximetry monitoring pathways for patients with COVID-19 in the English National Health Service.Design Retrospective, multisite, observational study of home oximetry monitoring for patients with suspected or proven COVID-19.Setting This study analysed patient data from four COVID-19 home oximetry pilot sites in England across primary and secondary care settings.Participants A total of 1338 participants were enrolled in a home oximetry programme across four pilot sites. Participants were excluded if primary care data and oxygen saturations at rest at enrolment were not available. Data from 908 participants were included in the analysis.Interventions Home oximetry monitoring was provided to participants with a known or suspected diagnosis of COVID-19. Participants were enrolled following attendance to emergency departments, hospital admission or referral through primary care services.Results Of 908 patients enrolled into four different COVID-19 home oximetry programmes in England, 771 (84.9%) had oxygen saturations at rest of 95% or more, and 320 (35.2%) were under 65 years of age and without comorbidities. 52 (5.7%) presented to hospital and 28 (3.1%) died following enrolment, of which 14 (50%) had COVID-19 as a named cause of death. All-cause mortality was significantly higher in patients enrolled after admission to hospital (OR 8.70 (2.53–29.89)), compared with those enrolled in primary care. Patients enrolled after hospital discharge (OR 0.31 (0.15–0.68)) or emergency department presentation (OR 0.42 (0.20–0.89)) were significantly less likely to present to hospital than those enrolled in primary care.Conclusions This study finds that home oximetry monitoring can be a safe pathway for patients with COVID-19; and indicates increases in risk to vulnerable groups and patients with oxygen saturations <95% at enrolment, and in those enrolled on discharge from hospital. Findings from this evaluation have contributed to the national implementation of home oximetry across England.